The importance and challenges of measuring work hours - Jay Stewart (IZA World of Labor, 2019)
Work hours are key components in estimating productivity growth and hourly wages as well as being a useful cyclical indicator in their own right, so measuring them correctly is important. The US Bureau of Labor Statistics (BLS) collects data on work hours in several surveys and publishes four widely used series that measure average weekly hours. The series tell different stories about average weekly hours and trends in those hours but qualitatively similar stories about the cyclical behavior of work hours. The research summarized here explains the differences in levels, but only some of the differences in trends.
Keywords: J22; C81; E23; 330; hours of work; household surveys; establishment surveys; time-use surveys; productivity; hourly wages